Geodetic and Geophysical Observations in Antarctica : An Overview in the IPY Perspective. - Capra, Alessandro. (Springer, 2017)
Due to their unique geophysical and geodynamic environment, both the Arctic and Antarctic polar regions are often utilized for geodetic and geophysical observations. This book is a collection of papers on various aspects of the scientific investigation and observation techniques of the polar regions at both temporary and permanent observatories. Most papers focus on regional models based on data acquired in polar regions. Geodetic satellite positions systems (GNSS: GPS, GLONASS, GALILEO) will also be discussed as well as other space techniques (DORIS, VLBI). Gravimetry, absolute gravimetry, and tidal gravimetry are also discussed, as well as seismology and meteorology. The book also touches on data analysis and geodynamic interpretation and discusses methods of constructing autonomous observatories.